Proceedings of the 1st Workshop on the Science of Cyberinfrastructure: Research, Experience, Applications and Models 2015
DOI: 10.1145/2753524.2753527
|View full text |Cite
|
Sign up to set email alerts
|

Science Gateway Canvas

Abstract: Science Gateways (SGs) have emerged as systems that facilitate access to cyberinfrastructures. There is a growing interest in the exploitation and development of SGs. However, it remains challenging to understand and design SG with the required properties because of the complex nature of SGs. Additionally, it is difficult to decide upon frameworks that can be used to build them. In this paper we propose the Science Gateway Canvas, a business reference model for SGs that embodies the common SG functions and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…There are many frameworks that can be used to build such systems. Shahand et al [9] have identified eleven frameworks explicitly exploited to develop Science Gateway including Apache Airavata, Catania SG Gateway, Globus, HUBzero(+Pegasus), ICAT Job Portal, and WS-PGRADE/gUSE. Such frameworks are quite diverse, e.g.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many frameworks that can be used to build such systems. Shahand et al [9] have identified eleven frameworks explicitly exploited to develop Science Gateway including Apache Airavata, Catania SG Gateway, Globus, HUBzero(+Pegasus), ICAT Job Portal, and WS-PGRADE/gUSE. Such frameworks are quite diverse, e.g.…”
Section: Related Workmentioning
confidence: 99%
“…The development of such environments aiming at facilitating scientists tasks is challenging from the system engineering perspective. Several technologies and skills are needed [8,9]. Moreover, (a) people having the requested expertise (mainly expertise related with IT) are not always available in the scientific contexts calling for VREs, and (b) technology is in continuous evolution thus offering new opportunities for implementing existing facilities in innovative ways or integrating innovative facilities in existing VREs.…”
Section: Introductionmentioning
confidence: 99%